2013
DOI: 10.1007/s11745-013-3784-4
|View full text |Cite
|
Sign up to set email alerts
|

Down‐Regulation of Hepatic Stearoyl‐CoA Desaturase‐1 Expression by Fucoxanthin via Leptin Signaling in Diabetic/Obese KK‐Ay Mice

Abstract: Stearoyl-coenzyme A desaturase-1 (SCD1) is a rate-limiting enzyme that catalyzes the biosynthesis of monounsaturated fatty acids from saturated fatty acids. Recently, SCD1 down-regulation has been implicated in the prevention of obesity, and the improvement of insulin and leptin sensitivity. In this study, we examined the effect of fucoxanthin, a marine carotenoid, on hepatic SCD1 in obese mouse models of hyperleptinemia KK-A(y) and leptin-deficiency ob/ob. In KK-A(y) mice, providing a diet containing 0.2 % fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 23 publications
3
30
0
Order By: Relevance
“…Down-regulation of hepatic SCD1 expression has been observed through leptin signalling (22). Beppu et al (22) indicated that suppression of the SCD index and SCD1 expression in the liver occurred in parallel with a lower serum leptin level as did the present results and our previous study (5).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Down-regulation of hepatic SCD1 expression has been observed through leptin signalling (22). Beppu et al (22) indicated that suppression of the SCD index and SCD1 expression in the liver occurred in parallel with a lower serum leptin level as did the present results and our previous study (5).…”
Section: Resultssupporting
confidence: 79%
“…It has been indicated that the serum TAG level was suppressed to around half by the pair-feeding and lower food intake in comparison with the case of the ad libitum feeding study (5). Down-regulation of hepatic SCD1 expression has been observed through leptin signalling (22). Beppu et al (22) indicated that suppression of the SCD index and SCD1 expression in the liver occurred in parallel with a lower serum leptin level as did the present results and our previous study (5).…”
Section: Resultssupporting
confidence: 72%
“…Indeed, in diabetic/obese KK-A y mice, FX (0.2% for 4 weeks) significantly decreased stearoyl-coenzyme A desaturase-1 mRNA and protein expression, body weight gain and serum leptin levels, as well as the hepatic oleic/stearic acid ratio [35]. The role of leptin in mediating the anti-obese effects of FX gained further support from the observation that they were completely abrogated in leptin-deficient ob/ob mice [35]. The FX-induced increase in expression of β3-adrenergic receptor in WAT could be an addition factor for enhancing lipogenesis in obese mice [34].…”
Section: Fx Stimulates Lipolysis and Inhibits Lipogenesismentioning
confidence: 96%
“…Its downregulation prevents obesity and improves sensitivity to insulin and leptin. Indeed, in diabetic/obese KK-A y mice, FX (0.2% for 4 weeks) significantly decreased stearoyl-coenzyme A desaturase-1 mRNA and protein expression, body weight gain and serum leptin levels, as well as the hepatic oleic/stearic acid ratio [35]. The role of leptin in mediating the anti-obese effects of FX gained further support from the observation that they were completely abrogated in leptin-deficient ob/ob mice [35].…”
Section: Fx Stimulates Lipolysis and Inhibits Lipogenesismentioning
confidence: 98%
“…Moreover, the last step of ALA to DHA conversion, C24:6n-3 to DHA, involved a peroxisomal β-oxidation which has been known to be regulated by PPARα. Woo et al (2010) reported that FX supplementation significantly increased mRNA of PPARα and its target gene acyl-CoA oxidase-1 (ACOX-1) in high fat diet-fed C57BL/6 N mice [27]. Beppu (2012) reported increased SREBP-1 and SREBP-2 protein in the liver of KK-A y mice fed the FX-containing diet [28].…”
Section: Discussionmentioning
confidence: 99%